2017
DOI: 10.1111/aogs.13257
|View full text |Cite
|
Sign up to set email alerts
|

Very tight vs. tight control: what should be the criteria for pharmacologic therapy dose adjustment in diabetes in pregnancy? Evidence from randomized controlled trials

Abstract: When evaluating RCTs which included criteria for pharmacologic GDM therapy dose adjustment, the most common criterion for diagnosis was the two-step test, and the most common used therapies were insulin and metformin. Regarding glucose monitoring, the most common frequency was four times per day, fasting and two hours after each main meal, using as target glucose values 95 and 120 mg/dL, respectively. Importantly, we found six different criteria for pharmacologic GDM therapy dose adjustment, with the majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 63 publications
(199 reference statements)
0
4
0
Order By: Relevance
“…Treatment initiation is proposed when either one or two blood glucose readings in a seven-to-14-day block are above set thresholds. Once treatment has been commenced criteria for dose adjustment of hypoglycaemic agents is equally contentious with six different strategies reported in one review [114,115]. As part of this study, we sought to determine glucose thresholds in our own population beyond which a benefit for hypoglycaemic agents was identified.…”
Section: Insulinmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment initiation is proposed when either one or two blood glucose readings in a seven-to-14-day block are above set thresholds. Once treatment has been commenced criteria for dose adjustment of hypoglycaemic agents is equally contentious with six different strategies reported in one review [114,115]. As part of this study, we sought to determine glucose thresholds in our own population beyond which a benefit for hypoglycaemic agents was identified.…”
Section: Insulinmentioning
confidence: 99%
“…The delivery of insulin for gestational diabetes as multiple daily injections has been found to be the most efficacious. Insulin dosages are adjusted based on glycaemic indices which are most frequently assessed four times a day [26,114].…”
Section: Insulinmentioning
confidence: 99%
“…Although therapy adjustment based on postprandial blood glucose levels is associated with improved outcomes 15 , there are currently no standardised criteria regarding the precise steps that should be taken to optimise glucose control. A recent meta-analysis identified RCTs which used various levels of strictness for intensifying glucose control, ranging from a single recorded value exceeding target values to more than 50% of recordings being above target values, and concluded that there is not enough evidence to recommend one approach over the other given the wide variations seen across the included studies 16 . A retrospective study by Scifres et al .…”
Section: Glycaemic Controlmentioning
confidence: 99%
“…The following values are published in the Australasian Diabetes in Pregnancy Society guidelines in the section 'for further research' and are followed by many, but by no means all, maternity centres: 4,25 • Fasting capillary blood glucose:…”
Section: Treatment Targetsmentioning
confidence: 99%